(untitled) (Revista de Medicina Clinica, 2025)
Background: Acute myocardial infarction (AMI) in young individuals without traditional cardiovascular risk factors is rare and should prompt evaluation for unusual causes. One such infrequent etiology is chronic myeloproliferative neoplasms (MPNs). Case Report: We present the case of a 33-year-old man admitted with non-ST elevation acute coronary syndrome (NSTE-ACS). Coronary angiography revealed no obstructive lesions, leading to a diagnosis of MINOCA (myocardial infarction with non-obstructive coronary arteries). A chest CT scan ruled out acute aortic syndrome but detected thrombi in the aorta and right common iliac artery. Laboratory studies revealed persistent thrombocytosis for at least four years, suggesting a chronic MPN. Further investigations—including autoimmune and thrombophilia screening, JAK2 mutation testing, and bone marrow biopsy—confirmed the diagnosis of polycythemia vera. Anticoagulation therapy was initiated. MPNs are known to increase the risk of both venous and arterial thrombotic events, including AMI and large-vessel thrombosis. These complications are associated with high morbidity and mortality, even in the absence of conventional cardiovascular risk factors. Conclusion: In young patients presenting with AMI or arterial thrombosis without identifiable cardiovascular risk factors, especially when persistent hematologic abnormalities are found, an underlying myeloproliferative neoplasm should be considered. Early diagnosis is crucial to guide appropriate management and reduce the risk of recurrence.